2012
DOI: 10.1002/cmdc.201200348
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Core Extension in the Series of N‐Cyclic Bay‐Substituted Perylene G‐Quadruplex Ligands: Increased Telomere Damage, Antitumor Activity, and Strong Selectivity for Neoplastic over Healthy Cells

Abstract: Based on previous work on both perylene and coronene derivatives as G-quadruplex binders, a novel chimeric compound was designed: N,N'-bis[2-(1-piperidino)-ethyl]-1-(1-piperidinyl)-6-[2-(1-piperidino)-ethyl]-benzo[ghi]perylene-3,4:9,10-tetracarboxylic diimide (EMICORON), having one piperidinyl group bound to the perylene bay area (positions 1, 12 and 6, 7 of the aromatic core), sufficient to guarantee good selectivity, and an extended aromatic core able to increase the stacking interactions with the terminal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Importantly, the effects of RHPS4 on EC function appeared to be principally mediated by a reduced expression of vegfr-2 : they recapitulated those observed by using a specific interference RNA against vegfr-2 (Figure 3D), and they were antagonized by overexpressing the vegfr-2 gene under the control of the CMV viral promoter (Figure 3E). The link between G4 ligand-mediated inhibition of vegfr-2 and impairment of EC functions was reinforced by using other chemically unrelated G4 ligands, Emicoron and PPL3C, two molecules, belonging to the coronene and perilene families of ligands, respectively (41,42). Consistently with the polymerase stop assay data, PPL3C and Emicoron caused a different degree of VEGFR-2 protein reduction and impairment of EC migration (Supplementary Figure S5A–C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the effects of RHPS4 on EC function appeared to be principally mediated by a reduced expression of vegfr-2 : they recapitulated those observed by using a specific interference RNA against vegfr-2 (Figure 3D), and they were antagonized by overexpressing the vegfr-2 gene under the control of the CMV viral promoter (Figure 3E). The link between G4 ligand-mediated inhibition of vegfr-2 and impairment of EC functions was reinforced by using other chemically unrelated G4 ligands, Emicoron and PPL3C, two molecules, belonging to the coronene and perilene families of ligands, respectively (41,42). Consistently with the polymerase stop assay data, PPL3C and Emicoron caused a different degree of VEGFR-2 protein reduction and impairment of EC migration (Supplementary Figure S5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are several novel aspects in our study, which include not only the discovery of a new G4-containg gene but also the functional relevance of this finding through intervention with small molecules, both in cell cultures and in animal model. Specifically, we found that a number of chemically unrelated G4 ligands (26,39,41,42) are able to bind to and stabilize the G4 structure identified within the promoter of vegfr-2, providing an explanation for their inhibitory effect on VEGFR-2 expression and on EC proliferation, migration, differentiation and in vivo angiogenesis. The effects of G4 ligands have been observed in human- and mouse-derived EC consistently with the presence of the G4 structure in both cell types (54) [as determined by the G4 prediction software QGRS (33)].…”
Section: Discussionmentioning
confidence: 95%
“…1A), having one piperidinyl group bound to the perylene bay area, sufficient to guarantee a good selectivity, and an extended aromatic core able to increase the stacking interactions with the ending tetrad of the G4. The subsequent profiling of its biologic properties demonstrated that this compound is outstandingly potent in inducing selective DNA damage to telomeres of cancer cells versus normal cells, endowing with efficient antiproliferative effect on several tumor cell lines at low micromolar concentrations (21). Moreover, in agreement with its ability to target the G4 sequence identified in the promoter of VEGFR-2 (22), EMICORON can bind to G4 structures throughout the genome (Fig.…”
Section: Introductionmentioning
confidence: 77%
“…perylene-3,4:9,10-tetracarboxylic diimide [EMICORON; molecular formula: C 52 H 59 N 6 O 4 .4HCl; molecular weight ¼ 977, estimated pK a (piperidine) ¼ 11] was synthesized as previously described (21) and used as a salt, specifically hydrochloride, with a good solubility in water. 7-Ethyl-10-hydroxycamptothecin (SN-38, Alexis) and doxorubicin (Ebewe) were also used.…”
Section: Methodsmentioning
confidence: 99%
“…In this direction, EMICORON is a very promising compound showing a good efficacy in vivo towards colon cancer models [117]. The compound destabilizes telomeric DNA but also downregulates both BCL2 and MYC by binding their promoters [118,119]. This broader activity may explain its efficacy.…”
Section: G-quadruplex and Cancermentioning
confidence: 99%